Persepsi Tentang Catcalling Yang Dialami Oleh Mahasiswa Universitas Dr. Soetomo Surabaya - Putri, Eka Dhanti Aprilia; Putro, Raden Hartopo Eko (Soetomo Communication and Humanities, 2022)
This study aims to determine the perception of catcalling experienced by students at Dr Soetomo University Surabaya. This study uses a qualitative descriptive research method with a case study approach. The data collection technique used is observation, namely making observations, interviews with resource persons and reading or viewing documents related to this research. The key informants who were used as resource persons were 5 people. And the results of this study indicate that the perception of catcalling experienced by university students Dr. Soetomo Surabaya is considered an act that leads to sexual harassment. This causes students who experience catcalling to feel fear.